Hi . here’s your answer. Step by step solution : STEP 1 : Equation at the end of step 1 ((x3) – 2×2) – 4x = 0 STEP 2 : STEP 3 : Pulling out like terms 3.1 Pull out like factors : x3 – 2×2 – 4x = x • (x2 – 2x – 4) Trying to factor by splitting the middle term 3.2 Factoring x2 – 2x – 4 The first term is, x2 its coefficient is 1 . The middle term is, -2x its coefficient is -2 . The last term, “the constant”, is -4 Step-1 : Multiply the coefficient of the first term by the constant 1 • -4 = -4 Step-2 : Find two factors of -4 whose sum equals the coefficient of the middle term, which is -2 . -4 + 1 = -3 -2 + 2 = 0 -1 + 4 = 3 Observation : No two such factors can be found !! Conclusion : Trinomial can not be factored. Hope it helped you. please mark this answer as brainiest. Reply

Hi .

here’s your answer.

Step by step solution :

STEP

1

:

Equation at the end of step 1

((x3) – 2×2) – 4x = 0

STEP

2

:

STEP

3

:

Pulling out like terms

3.1 Pull out like factors :

x3 – 2×2 – 4x = x • (x2 – 2x – 4)

Trying to factor by splitting the middle term

3.2 Factoring x2 – 2x – 4

The first term is, x2 its coefficient is 1 .

The middle term is, -2x its coefficient is -2 .

The last term, “the constant”, is -4

Step-1 : Multiply the coefficient of the first term by the constant 1 • -4 = -4

Step-2 : Find two factors of -4 whose sum equals the coefficient of the middle term, which is -2 .

-4 + 1 = -3

-2 + 2 = 0

-1 + 4 = 3

Observation : No two such factors can be found !!

Conclusion : Trinomial can not be factored.

Hope it helped you.

please mark this answer as brainiest.